Modified posterolateral approach for fixation of posterior malleolar fractures associated with distal tibiofibular syndesmosis injury: A surgical technique - Marinho Guimarães, Beatriz; Lemos, André Vitor Kerber Cavalcanti; Nery, Caio Augusto de Souza; Ambrosio, Gustavo Henrique Carillo; Maciel, Eduardo Souza (Journal of the Foot & Ankle, 2025)
Posterior malleolar fractures are challenging to treat in ankle injuries and, when not treated properly, can lead to unfavorable results, especially if associated with syndesmosis injury. Posterior access approaches (posterolateral and posteromedial) are recommended for reduction and adequate fixation of the posterior malleolus; however, they usually do not allow direct visualization of the syndesmosis, one of the main prognostic factors in the treatment of these injuries. We present a modified posterolateral approach that enables direct visualization of the syndesmosis, in addition to the use of syndesmosis fixation implants integrated with lateral implants when associated with a lateral malleolar fracture. Level of evidence IV; Case series